Plasma FGF23 levels and heart rate variability in patients with stage 5 CKD - Zhang, L.-N.; Yang, G.; Cheng, C.; Shen, C.; Cui, Y.-Y.; Zhang, J.; Zhang, J.-J.; Shen, Z.-X.; Zeng, M.; Ge, Y.-F.; Sun, B.; Yu, X.-B.; et al. (Osteoporosis international, 2015)
Summary Fibroblast growth factor 23(FGF23) is a bone-derived hormone which regulates mineral homeostasis but may also have a role in cardiovascular disease. Here, we found that higher plasma FGF23 was independently associated with decreased heart rate variability in stage 5 CKD patients and parathyroidectomy may reverse these abnormal indicators. Introduction Lower heart rate variability (HRV) in patients with chronic kidney disease (CKD) compared with healthy controls is associated with increased risk of cardiovascular disease (CVD). Higher levels of plasma FGF23 also predict higher risk of CVD. Here, we aimed to evaluate the relationship between plasma FGF23 levels and HRV in patients with stage 5 CKD and to investigate longitudinal changes of them together with the correlation between their changes in two severe secondary hyperparathyroidism (SHPT) subgroups with successful parathyroidectomy (PTX) and persistent SHPT. Methods This cross-sectional study included 100 stage 5 CKD patients, 78 controls, and a prospective study in two PTX subgroups classified as successful PTX ( n = 24) and persistent SHPT ( n = 4) follow-up. Blood examination and 24-h Holter monitoring for HRV were measured. Results Most HRV indices were lower in stage 5 CKD patients than in healthy controls, and plasma FGF23 levels were higher. In multivariate stepwise regression models, levels of plasma FGF23 and serum parathyroid hormone (PTH) were correlated with HRV. The successful PTX subgroup had significant improvements over baseline in HRV indices. Persistent SHPT subgroup had numerically similar changes in HRV indices. However, plasma FGF23 levels decreased in both subgroups. Conclusions Plasma FGF23 levels were higher in CKD patients than in controls, much higher in patients with severe SHPT. FGF23 was independently associated with decreased HRV in stage 5 CKD. Successful PTX may reverse these abnormal indicators and contribute to decreases in the risk of cardiovascular disease.